Bassoon and piccolo regulate ubiquitination and link presynaptic molecular dynamics with activity‐regulated gene expression. (24th April 2016) - Ivanova, Daniela; Dirks, Anika; Fejtova, Anna
Abstract : Modifications of the presynaptic cytomatrix: temporal and spatial relationships. Neuronal activity and extracellular cues can induce alterations in the composition of the presynaptic molecular machinery, in different temporal and spatial frames, depending on the involved cellular mechanisms. Activation of signalling cascades leads to posttranslational modifications by phosphorylation, dephosphorylation and ubiquitin and SUMO conjugations, which rapidly modulate protein–protein interactions and thereby the composition and the function of the presynaptic macromolecular complexes with a high local selectivity. In addition, the posttranslational modifications are a trigger for local protein synthesis and degradation, which contribute to the molecular remodelling of the presynaptic functional machineries. Several pathways mentioned in this article mediate synapse to nucleus communication necessary for long‐range coupling of signalling events at the presynapse with reconfiguration of gene expression in the neuronal nucleus. Common features of these pathways are the local generation/activation of signalling molecules in axons, their retrograde trafficking and their effect on gene expression in the nucleus. Abstract: Release of neurotransmitter is executed by complex multiprotein machinery, which is assembled around the presynaptic cytomatrix at the active zone. One well‐established function of this proteinaceous scaffold is the spatial organization of synaptic vesicle cluster, the protein complexes that execute membrane fusion and compensatory endocytosis, and the transmembrane molecules important for alignment of pre‐ and postsynaptic structures. The presynaptic cytomatrix proteins function also in processes other than the formation of a static frame for assembly of the release apparatus and synaptic vesicle cycling. They actively contribute to the regulation of multiple steps in this process and are themselves an important subject of regulation during neuronal plasticity. We are only beginning to understand the mechanisms and signalling pathways controlling these regulations. They are mainly dependent on posttranslational modifications, including phosphorylation and small‐molecules conjugation, such as ubiquitination. Ubiquitination of presynaptic proteins might lead to their degradation by proteasomes, but evidence is growing that this modification also affects their function independently of their degradation. Signalling from presynapse to nucleus, which works on a much slower time scale and more globally, emerged as an important mechanism for persistent usage‐dependent and homeostatic neuronal plasticity. Recently, two new functions for the largest presynaptic scaffolding proteins bassoon and piccolo emerged. They were implied (1) in the regulation of specific protein ubiquitination and proteasome‐mediated proteolysis that potentially contributes to short‐term plasticity at the presynapse and (2) in the coupling of activity‐induced molecular rearrangements at the presynapse with reprogramming of expression of neuronal activity‐regulated genes.